Two stages of late Paleoproterozoic A-type granites at the southern North China Craton: geochemical constraints and implications for supercontinent breakup - Wang, Zhiyi; Zhao, Jingxin; Qi, Zeqiu; Huo, Dongyang; Siebel, Wolfgang; He, Jun; Li, Shuang-Qing; Chen, Fukun (Precambrian research, 2024)
Paleoproterozoic and Mesoproterozoic A-type granites occur on many cratons and possess important information for our understanding of the formation and breakup history of the supercontinent Columbia. It was argued previously, that Proterozoic A-type granites (∼1.8-1.5 Ga), exposed along the southern margin of the North China Craton formed in a post-collisional or anorogenic setting related to the final amalgamation of the North China Craton or to the breakup of Columbia. In the present study, we report zircon ages and geochemical data of the Maping A-type granite. This intrusion consists of a quartz monzonite porphyry and a granite porphyry that, based on U-Pb age dating, formed at ∼ 1.65 and ∼ 1.60 Ga, respectively. The granites show high contents in alkaline and high field strength elements, high Ga/Al and Fe/Mg ratios. The quartz monzonite porphyry of the early stage is metaluminous and relatively depleted in Hf-Nd isotopic compositions (whole-rock initial εNd values −5.4 to −4.5; zircon initial εHf values −8.5 to −1.5), while granite porphyry of the late stage is peraluminous and has lower initial εNd and εHf values (−6.4 to −5.9; −9.6 to −3.3). Inherited zircon grains in the Maping intrusion have relatively high initial εHf values (>-0.7), likely originating from juvenile crust. The Pb isotopes of the quartz monzonite porphyry show characteristics similar to the lower crust, whereas the granite porphyry has more radiogenic Pb isotopic compositions. Apatite grains from the quartz monzonite porphyry have initial 87Sr/86Sr ratios of ∼ 0.7109-0.7133 and those from the granite porphyry have noticeably high initial 87Sr/86Sr ratios of ∼ 0.7862-0.8812. These isotopic characteristics imply the presence of various crustal rocks underneath the North China Craton with variable isotopic compositions. From the early to late magmatic stages, the Sr/Y ratios of granitic rocks decrease from 1.6 - 7.6 to 0.2-0.4, while the estimated magma temperatures, calculated from whole-rock compositions, slightly increase from approximately 900 °C to about 930 °C. These concurrent changes in temperature and chemical composition reflect ongoing asthenospheric mantle upwelling during crustal extension. This suggests a transition in the southern margin of the North China Craton from a post-collisional setting before 1.65 Ga to an anorogenic setting by 1.6 Ga.
Gesehen am 18.06.2025